Press Freedom and the Espionage Act: A Critical Juncture - Ethan Thompson (Washington University Journal of Law & Policy, 2021)
Historically, the number of media leak prosecutions under the Espionage Act have been infrequent. The number of prosecutions, however, has been rising in recent years. This Note details the 2019 indictment of Wikileaks founder, Julian Assange. Thompson proposes a statutory framework that aims to balance the government’s legitimate interest in protecting classified information with the public benefit resulting from the disclosure. Thompson’s proposal would allow courts to distinguish espionage and acts that threaten U.S. Security from leaks that serve the public interest. This Note analyzes the history of the Espionage Act, the critical juncture determining how future prosecutions under the Espionage Act will be conducted, and proposed policy and legal recommendations to protect the freedom of the press and allow news outlets to perform their vital democratic function of keeping the public informed of government action.
Keywords: Espionage Act; Wikileaks; Julian Assange; press freedom; freedom of the press; press; news; public; public information; information; First Amendment; journalism; security; national security